Isolation of the galactose-binding lectin that mediates the in vitro adherence of Entamoeba histolytica. - Petri, W A, Jr; Smith, R D; Schlesinger, P H; Murphy, C F; Ravdin, J I (The Journal of Clinical Investigation, 1987)
Entamoeba histolytica adheres to human colonic mucus, colonic epithelial cells, and other target cells via a galactose (Gal) or N-acetyl-D-galactosamine (GalNAc) inhibitable surface lectin. Blockade of this adherence lectin with Gal or GalNAc in vitro prevents amebic killing of target cells. We have identified and purified the adherence lectin by two methods: affinity columns derivatized with galactose monomers or galactose terminal glycoproteins, and affinity columns and immunoblots prepared with monoclonal antibodies that inhibit amebic adherence. By both methods the adherence lectin was identified as a 170-kD secreted and membrane-bound amebic protein. The surface location of the lectin was confirmed by indirect immunofluorescence. Purified lectin competitively inhibited amebic adherence to target cells by binding to receptors on the target Chinese hamster ovary cells in a Gal-inhibitable manner. Images